Floating s- and p-type Gaussian Orbitals - Brailsford, David F.; Hall, G. G.; Hemming, N.; Martin, D. (Elsevier, 1975)
The advantages of including a small number of p-type gaussian functions in a floating spherical gaussian orbital calculation are pointed out and illustrated by calculations on molecules which previously have proved to be troublesome. These include molecules such as F2 with multiple lone pairs and C2H2 with multiple bonds. A feature of the results is the excellent correlation between the orbital energies and those of a double zeta calculation reported by Snyder and Basch.